Comparative efficacy and tolerability of pharmacological interventions for attention-deficit/hyperactivity disorder in children, adolescents and adults: protocol for a systematic review and network meta-analysis - Cortese, Samuele; Adamo, Nicoletta; Mohr-Jensen, Christina; Hayes, Adrian J.; Bhatti, Sahar; Carucci, Sara; Del Giovane, Cinzia; Atkinson, Lauren Z.; Banaschewski, Tobias; Simonoff, Emily; Zuddas, Alessandro; Barbui, Corrado; et al. (BMJ Publishing Group, 2017)
Introduction Attention-deficit/hyperactivity disorder (ADHD) is a major public health issue. Pharmacological treatments play an important role in the multimodal treatment of ADHD. Currently, there is a lack of up-to-date and comprehensive evidence on how available ADHD drugs compare and rank in terms of efficacy and tolerability, in children or adolescents as well as in adults. We will conduct a network meta-analysis (NMA), integrating direct and indirect comparisons from randomised controlled trials (RCTs), to rank pharmacological treatments for ADHD according to their efficacy and tolerability profiles.